Improving students listening achievement through information transfer technique in senior high school - Fernanda, Muhammad Fajri; Flora; Shafwati, Dian (U-Jet Unila Journal of English Language Teaching, 2024)
Listening is one of the four language skills students should master since it is a vital skill for students to strengthen their language skills, especially English. The main problem of this research was students' lack of listening skills. The objective of the research was to find out whether or not information transfer can improve students' listening achievement among the second-grade students of Senior High School 9 in Bandar Lampung. The method used in this study was the experimental method with a pre-test post-test one-group design. Data were analysed using the paired-sample t-test formula. The population for this research was drawn from the second-grade students of Senior High School 9 Bandar Lampung, academic year 2021/2022. The sample tested consisted of 30 students from class XI IPA 1, selected through simple random sampling. The findings of this study showed that the average score in the pre-test was 17.17, with the lowest score achieved being 33.3 and the highest score achieved being 80. In the post-test, the average score was 22.50, with the lowest score achieved being 53.3 and the highest score achieved being 90. The result of the paired sample t-test was 0.000, which was lower than 0.05. This indicates that the null hypothesis (Ho) was accepted, and the alternative hypothesis (Ha) was rejected. Based on the results of the data analysis, it was found that teaching listening using the information transfer technique to second-grade students at Senior High School 9 of Bandar Lampung was effective.